HEGEMONI DALAM NOVEL MARYAM KARYA OKKY MADASARI: KAJIAN HEGEMONI GRAMSCI - Safitri, Dwi; Fatimah, Siti; Sidiq Budiawan, R. Yusuf (Universitas Muhammadiyah Surabaya, 2024)
This research aims to describe the hegemony of power in the novel